REMOTE SENSING, GIS AND PUBLIC HEALTH - HIROKl SUGIMORI (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2004)
The role of remote sensing (RS) and Geographic Information Systems (GIS) in public health is potentially great. As computer technology it continues to transform our ability to gather, analyze, and map health data, new roles for RS and GIS in public health may emerge. Keywords: Public Health, Disease Mapping